2008
DOI: 10.1128/jb.01813-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Type IV Secretion Apparatus Genes during Ehrlichia chaffeensis Intracellular Development by a Previously Unidentified Protein

Abstract: The type IV secretion (T4S) system is critical for the virulence of several pathogens. In the rickettsial pathogen Ehrlichia chaffeensis, the virBD genes are split into two operons, the virB3-virB6 (preceded by sodB) and virB8-virD4 operons. Between these two operons, there are duplications of virB4, virB8, and virB9. In this study we found that transcription of all five loci was downregulated prior to the release of E. chaffeensis from host THP-1 cells and was upregulated at the initiation of exponential grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 38 publications
7
87
0
Order By: Relevance
“…Similar to the findings of our previous study (4), when E. chaffeensis was synchronously cultured, bacteria became visually detectable after a long lag phase (ϳ24 to 36 h postinfection [p.i.]). Small (Ͻ1-m) dense morulae were detected in Ͼ80% of host cells at 57 h p.i.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similar to the findings of our previous study (4), when E. chaffeensis was synchronously cultured, bacteria became visually detectable after a long lag phase (ϳ24 to 36 h postinfection [p.i.]). Small (Ͻ1-m) dense morulae were detected in Ͼ80% of host cells at 57 h p.i.…”
Section: Resultssupporting
confidence: 79%
“…We previously reported that an E. chaffeensis transcription factor, EcxR, regulates the expression of genes encoding type IV secretion machinery during the exponential growth stage of E. chaffeensis (4). To examine whether pleC and pleD are coregulated by EcxR, EMSA was performed using rEcxR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in A. phagocytophilum and E. chaffeensis (but not Rickettsia spp. ), sodB, encoding an iron superoxide dismutase, is cotranscribed with the virB3-virB6 genes (60,207). A protective oxidative stress response might thus be coupled with T4SS machine assembly in environments, e.g., the eukaryotic cytoplasm or blood-feeding ticks, where both activities are needed for cell survival or proliferation.…”
Section: More Gram-negative Systemsmentioning
confidence: 99%
“…T4SSs are encoded by a single polycistronic transfer region in most bacteria, while in others they are encoded as split loci (6). The genes in the transfer region usually have overlapping stop-and-start codons, which allows the expression of a large set of genes from a few promoters and regulation of both transcription and translation.…”
Section: Vol 192 2010 Expression Of Gonococcal T4ss Genes 1917mentioning
confidence: 99%